2023
DOI: 10.1186/s40104-023-00913-5
|View full text |Cite
|
Sign up to set email alerts
|

The type of lipid supplement has crucial implications for forage particle size in calf starter diets

Pedram Panahiha,
Hamidreza Mirzaei-Alamouti,
Mehdi Kazemi-Bonchenari
et al.

Abstract: Background Forage inclusion in starters of young dairy calves has become an acceptable strategy in the last decade. To compensate for the lower energy provided by forage, concurrent lipid supplementation can be proposed. However, ruminal microbial activity and forage digestibility may be decreased by lipid supplementation. We hypothesized that the composite effect of forage and lipid supplements may be dependent on forage particle size and the type of lipid supplement. Therefore, we evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…However, results are partly divergent. Panahiha et al [6,7] showed that performance improved by supplementing palm fatty acids compared with soybean oil in the starter diet. In contrast, Hill et al [3,4] showed that ADG increased by adding sources of n-3 PUFA (C18:2 and C18:3) to the SF in calves up to 120 days of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results are partly divergent. Panahiha et al [6,7] showed that performance improved by supplementing palm fatty acids compared with soybean oil in the starter diet. In contrast, Hill et al [3,4] showed that ADG increased by adding sources of n-3 PUFA (C18:2 and C18:3) to the SF in calves up to 120 days of life.…”
Section: Discussionmentioning
confidence: 99%
“…Hill et al [3][4][5] demonstrated that adding a blend of FAs, including polyunsaturated FAs (PUFAs), to the starter feed (SF) or milk replacers could enhance growth performance parameters while reducing scouring and respiratory disease occurrence rates in young calves. Panahiha et al [6,7] found that supplementing the starter diet with palm fatty acids (saturated fatty acid source) compared to soybean oil (n-6 FA source) had superior effects on the performance of young calves before weaning. It is well documented that FAs from n-3 PUFAs possess anti-inflammatory properties, which may partly explain the lower incidences of diseases when supplemental n-3-rich oils are provided [8].…”
Section: Introductionmentioning
confidence: 99%